Modern methods of assessing the risks of managing the enterprise's financial flows in crisis - Babenko, Vladyslav (My University, 2023)
The market mechanisms of the functioning of the economy of any state are cyclical. The economic results of each enterprise are formed under the influence of these macroeconomic fluctuations, and also depend on the action of many internal reasons. Ensuring stable and harmonious economic growth of Ukraine's economy makes extremely urgent issue of organizing counter measures against crisis phenomena and reviving the normal course of functioning of the main link of the economy enterprises of various forms of ownership and management. It requires mastering and implementation in the practice of anti crisis management. The high probability of the occurrence and development of a crisis in the course of the activity of any enterprise necessitates the implementation of specialized anticrisis management, which is aimed at overcoming crisis phenomena, based on systemic, situational and process approaches.
Keywords: enterprise management; crisis; risk; enterprise; finance